2014
DOI: 10.1158/1078-0432.ccr-13-2671
|View full text |Cite
|
Sign up to set email alerts
|

Is the “3+3” Dose-Escalation Phase I Clinical Trial Design Suitable for Therapeutic Cancer Vaccine Development? A Recommendation for Alternative Design

Abstract: Purpose Phase 1 clinical trials are generally conducted to identify the maximum tolerated dose (MTD) or the biologically active dose (BAD) using a traditional dose escalation design. This design may not be applied to cancer vaccines, given their unique mechanism of action. The FDA recently published “Guidance for Industry: Clinical Considerations for Therapeutic Cancer Vaccines.” However, many questions about the design of cancer vaccine studies remain unanswered. Experimental Design We analyzed the toxicity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Imiquimod is not approved for use in topical treatment of melanoma metastases, but its off-label use has been reported in that setting (18, 28, 29), with beneficial control of treated lesions in some patients. Cancer vaccines have a very favorable safety profile (30) so the present study is consistent with prior work supporting safety of vaccines plus imiquimod in combination.…”
Section: Discussionsupporting
confidence: 89%
“…Imiquimod is not approved for use in topical treatment of melanoma metastases, but its off-label use has been reported in that setting (18, 28, 29), with beneficial control of treated lesions in some patients. Cancer vaccines have a very favorable safety profile (30) so the present study is consistent with prior work supporting safety of vaccines plus imiquimod in combination.…”
Section: Discussionsupporting
confidence: 89%
“…Most have a safety profile that is better than that of traditional cancer chemotherapies, with clinically significant adverse events being either not observed or only mild (1820) (21). This of course is predicated on the ability to elicit a strong immune response in the setting of cancer.…”
Section: Review Of the Recommendations And Discussionmentioning
confidence: 99%
“…Accordingly, testing for acute toxicity in a phase 1 safety trial would be needed in the following categories: 1) any vaccine with substantial toxicity observed in preclinical toxicity studies; 2) classes of vaccine platforms with toxicity demonstrated in previously conducted clinical trials and 3) new vaccine platforms or other vaccine components (e.g. adjuvant) with potential vital organ toxicity (21). Since induction of autoimmunity is one of the safety issues that have been associated with some cancer vaccines, assessment of this issue in the earliest stage or NED patients with greater immune competence, is much more likely to be informative.…”
Section: Review Of the Recommendations And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Food and Drug Administration (FDA) recently published a “Guidance for Industry: Clinical Considerations for Therapeutic Cancer Vaccines,” which acknowledged the need for alternative dose-escalation methods in cancer vaccines [10, 11]. In contrast to chemotherapeutic agents, dose-finding in immunotherapy often investigates treatments that demonstrate minimal toxicity overall, where higher doses may not induce greater immunologic effect.…”
Section: Designing Immunotherapy Trialsmentioning
confidence: 99%